Namibia : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation highlights that Namibia recorded robust real GDP growth, falling inflation, a strong external current account surplus, and continued low external indebtedness over the last two years. Real GDP grew by 6 percent in 2004, as new marine technologies prompted a surge in diamond production and most other sectors of the economy showed solid economic activity, aided by a decline in interest rates. Growth slowed in 2005, as diamond production fell relative to the high production base of the previous year and growth rates in other sectors moderated somewhat.